2020
DOI: 10.1002/acr.23928
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Opioid Use Among Patients With Acute Gout Discharged From the Emergency Department

Abstract: Objective. Acute gout is among the most painful inflammatory arthritides and a frequent cause of emergency department (ED) visits. Prescription opioids are the leading contributor to the ongoing opioid epidemic; EDs are often the source of the index prescription. Our aim was to assess the burden of opioid use and factors associated with its use among gout patients discharged from the ED.Methods. In the electronic health records system of Lifespan Healthcare System (currently contains 2.2 million records), adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…With the current opioid epidemic, it is important to consider that uncontrolled gout may also serve as a gateway to opioid use. A recent study using electronic health records from the state of Rhode Island found that nearly 30% of patients who were treated in the emergency department with a primary diagnosis of gout were prescribed opioid therapy at discharge (5). This opioid prescription rate is nearly twice what is observed in emergency departments across all medical conditions (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the current opioid epidemic, it is important to consider that uncontrolled gout may also serve as a gateway to opioid use. A recent study using electronic health records from the state of Rhode Island found that nearly 30% of patients who were treated in the emergency department with a primary diagnosis of gout were prescribed opioid therapy at discharge (5). This opioid prescription rate is nearly twice what is observed in emergency departments across all medical conditions (49).…”
Section: Discussionmentioning
confidence: 99%
“…These figures have grown with 2012 estimates using the same data source demonstrating >200,000 gout‐related emergency department visits, with encounter‐related charges exceeding $280 million (4). This increase in gout‐related emergency department visits is particularly relevant, as almost one‐third of patients with gout seen in the emergency department receive an opioid prescription at discharge (5), suggesting that gout may serve as a gateway to chronic opiate use even though highly effective gout therapies are available. In addition to direct health care costs and costs posed by potentially inappropriate care, gout is also independently associated with increased work absenteeism and losses in work productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there is almost no role for opioid analgesics in the management of acute gout. Yet both the studies, by Dr. Schlesinger’s group and ours, report that approximately one‐third of patients with acute gout in the ED receive opioid prescriptions at discharge (1,4). There are 3 aspects of this observation that are particularly interesting and that warrant further investigations.…”
mentioning
confidence: 86%
“…We would like to thank the editors for providing us an opportunity to further the discussion regarding opioid use for management of acute gout and thank Dr. Schlesinger and colleagues for highlighting yet another study describing the burden of opioid prescription for gout management (1). As appropriately pointed out, opioids do not reduce the inflammation of an acute gout attack, and conventional antiinflammatories like colchicine, nonsteroidal antiinflammatory drugs, and steroids can substantially reduce pain within the first 24 hours of administration (2,3).…”
Section: Replymentioning
confidence: 99%